Desain Tapak Perkemahan Konservasi di Laboratorium Lapangan Konservasi Sumberdaya Hutan dan Ekowisata Hutan Pendidikan Unhas - Amran Achmad; Ngakan Putu Oka; Roland Barkey; Nida Sari Achmad (Forestry Faculty of Universitas Hasanuddin, 2018)
This study aims to design a conservation campsite that comfortable and attractive, which is also as a place of education for the conservation of natural resources and their ecosystems. This research was conducted at the Field Laboratory of Forest Resources Conservation and Ecotourism Unhas Educational Forest. Field data collection of altititude was done by using a systemic sampling method on 358 sample points, with the distance between each sample point was 10 m. Data was processed by Digital Elevetaion Model (DEM). The results are then used to create a map of the slopes and contours. The location of tents and other camp facilities, set based on the direction of the view that shows open views, elevation position with height difference based on the height of the tent, the shape of the tent (dom and platoon), distance between tents, slope classes, other campground facilities, such as toilets, public kitchens , cultural stage, as well as activities in conservation camps such as games, campfires, and others. The results showed that conservation camps at the Field Laboratory of Forest Resources Conservation and Ecotourism, were divided into four camp blocks. Block I accommodates eight tents that placed in the three rows, eight tents in block II in two rows, and 23 tents in block III in a position of four rows. For block IV prepared for tent tents, with a capacity of four tents in a two-row position. The campground facilities are in the form of cultural stage, resting area, musallah, management house and public kitchen, toilet, gazebo, and sports field. The design of field learning related to conservation involves three themes, namely (a) the introduction of biological natural resources and their ecosystems, (b) the introduction of ecology, and (c) conservation area management.Key words: Field Design, Campground, Conservation Education.